Bio-economics of Cropping Systems Combining Medicinal and Aromatic Herbs with Commercial Timber Tree Species - Dutt, Vaishnu; Thakur, P. S. (Indian Journal of Agroforestry, 2020)
The objective of this study was to ascertain monetary status of cropping systems, practiced for two consecutive years under Shivalik Ranges of outer Himalayas, combining medicinal and aromatic herbs with commercial timber species. Four herbal crops namely Ocimum sanctum, Spilanthes acmella, Tagetes minute and Withania somnifera were intercropped for two consecutive years with 6-year old plantation of Populus hybrid (G-48) having 8x3m, 6x4m, 5x5m and 4x 6m spacings. Net returns was comparatively more under agroforestry systems combining Ocimum sanctum and Tagetes minuta with poplar at different spacings in comparison to monocropping. However, in case of Spi/anthes acmella, the net returns were higher from sole cropping in comparison to agroforestry intervention. The net returns from Withania somnifera were negative both when the crop was raised as pure or intercropped with poplars (reason, high cost of cultivation). The combination of Withania somnifera + poplar at different spacings, however, resulted in considerable income from the system. Among different spacings, 8 x 3 m and 6 x 4 m spacings excelled over 5 x 5 and 4 x 6 m spacings, which ensured significantly higher net returns from the combination. From economic perspective point, medicinal and aromatic crops can be categorized as Spilanthes acmella > Ocimum sanctum> Tagetes minuta > Withania somnifera.